ANALISA pH, Fe, Mn PADA SUMBER AIR PANTI ASUHAN AISYIYAH KOTO TANGAH - Femi Earnestly; Muchlisinalahuddin Muchlisinalahuddin; Helga Yermadona (JURNAL KATALISATOR, 2022)
The source of the orphanage's well water is low quality, so the orphanage does not use the water for drinking purposes and only for other purposes such as bathing, washing, toileting and cooking. The purpose of this study was to analyze the well water quality of the Aisyiyah Orphanage, Koto Tangah based on chemical parameters including pH, iron and manganese levels according to the Regulation of Health Minister Republic Indonesia Number 32 of 2017. Sampling was carried out at two well sources with a sample point distance of about 150 m with purposive sampling method. As for testing pH, iron and manganese levels are in accordance with SNI: 06-6989.11-2019 and SNI: 06-6989.4-2019. The results of testing the quality of the well water are 1) pH testing for all points ranging from 7.18-7.72 which is still within the maximum limit level between 6.0-9.0. 2) Testing the iron content of well sample 1 (0.156 g/mL) and well sample 2 (3.371 mg/L), it was found that sample 1 was still below the threshold value while well sample 2 exceeded the threshold value set by the Minister of Health of the Republic of Indonesia number 32 of 2017. 3) Tests for manganese levels were found to be <0.038 mg/L and were still below the threshold of 0.5 mg/L. It is hoped that this data will become additional valuable information for the managers and children of the Aisyiyah Orphanage, Koto Tangah Padang